4. The Ways of Artistically Gifted Children's Identification in Primary Education - Bularga Tatiana; Avram Alina Ionela (Sciendo, 2022)
The article is dedicated to the problem of giftedness' identification in the educational process. The principal motivation for this thesis is the lack of pedagogical technologies which ensure the effective identification of gifted children and the unsounding of education practice in the development of musical talent where the first step must be treated its effective and objective identification. Has been proved the pedagogical prospect for practice implication, which combines a sequence of giftedness' abilities.